Review of the Neotropical species of Nervijuncta Marshall, 1896 (Diptera, Ditomyiidae) - Falaschi, Rafaela Lopes; de Souza Amorim, Dalton (Zootaxa, 2009)
Both known Neotropical species of Nervijuncta – N. conjuncta (Freeman) and N. laffooni Lane – are redescribed and the male terminalia illustrated in detail. Specimens of N. laffooni, previously known only from the type-locality (São Paulo, Brazil), are reported from Nova Teutônia, and Urubici, both in the State of Santa Catarina, Brazil. The females of both Neotropical species of the genus are described in detail and the genitalia illustrated for the first time. These redescriptions provide further information on the position of these two species within the genus.